2012
DOI: 10.1186/1471-2466-12-69
|View full text |Cite|
|
Sign up to set email alerts
|

Singing classes for chronic obstructive pulmonary disease: a randomized controlled trial

Abstract: BackgroundThere is some evidence that singing lessons may be of benefit to patients with chronic obstructive pulmonary disease (COPD). It is not clear how much of this benefit is specific to singing and how much relates to the classes being a group activity that addresses social isolation.MethodsPatients were randomised to either singing classes or a film club for eight weeks. Response was assessed quantitatively through health status questionnaires, measures of breathing control, exercise capacity and physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(119 citation statements)
references
References 33 publications
(34 reference statements)
2
109
2
2
Order By: Relevance
“…Lord et al 10,11 reported positive findings from health status measures, in particular a significant reduction in anxiety, a finding which was replicated in other studies 14,15 . While this is a positive finding where sample numbers are adequate, Engstrom et al 16 have suggested that generic self-assessment questionnaires are of limited value in detecting the early effects of COPD.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Lord et al 10,11 reported positive findings from health status measures, in particular a significant reduction in anxiety, a finding which was replicated in other studies 14,15 . While this is a positive finding where sample numbers are adequate, Engstrom et al 16 have suggested that generic self-assessment questionnaires are of limited value in detecting the early effects of COPD.…”
Section: Introductionmentioning
confidence: 73%
“…The theory of interrelated mechanisms has also been put forward in previous work. Lord 10,11 , for example, has suggested that perceived improvements in breathing may be largely psychologically mediated, which participants here seemed aware of.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…The present data 2,4 and this study suggest that singing does produce specific benefits and that participation in singing classes should be encouraged where these are available.…”
Section: Letter To the Editormentioning
confidence: 99%